Strategy to increase customer loyalty through customer satisfaction at abuba steak, Bekasi city - Rusman Efendi Sihombing; Verry Cyasmoro; Sandi Sutriana (Jurnal Mantik, 2026)
The objective of this study was to determine the effect of Brand Equity, Product Quality, and Servicescape on customer loyalty through customer satisfaction among Abuba Steak customers in Bekasi City. Prior studies have examined brand equity, product quality, and servicescape separately, with limited integration into a comprehensive model. Evidence from casual dining steakhouses in emerging markets remains scarce, and findings on customer satisfaction as a mediator are inconsistent. This study used a quantitative approach with the Structural Equation Modeling (SEM) method based on Partial Least Square (PLS). The sample in this study amounted to A total of 250 participants were chosen through intentionally selected based on predefined criteria, namely purchasers who have consumed exceeding two times. This research resulted in Brand Equity, Product Quality, and Servicescape having a significant influence on Customer Satisfaction and Customer Loyalty. In addition, Customer Satisfaction was shown to play a role as a mediating variable. on the relationship between Brand Equity, Product Quality and Servicescape on Customer Loyalty. This study contributes to the literature by proposing a holistic framework that integrates cognitive, functional, and experiential determinants of customer loyalty, while also providing empirical evidence on the mediating role of customer satisfaction in the underexplored context of casual dining steakhouse in an emerging market.